Assessing demographic access to hip replacement surgery in the United Kingdom: a systematic review - Sebastian Ryan-Ndegwa; Reza Zamani; Mohammad Akrami (BMC, 2021)
Abstract Persisting evidence suggests significant socioeconomic and sociodemographic inequalities in access to medical treatment in the UK. Consequently, a systematic review was undertaken to examine these access inequalities in relation to hip replacement surgery. Database searches were performed using MEDLINE, PubMed and Web of Science. Studies with a focus on surgical need, access, provision and outcome were of interest. Inequalities were explored in the context of sociodemographic characteristics, socioeconomic status (SES), geographical location and hospital-related variables. Only studies in the context of the UK were included. Screening of search and extraction of data were performed and 482 articles were identified in the database search, of which 16 were eligible. Eligible studies consisted of eight cross-sectional studies, seven ecological studies and one longitudinal study. Although socioeconomic inequality has somewhat decreased, lower SES patients and ethnic minority patients demonstrate increased surgical needs, reduced access and poor outcomes. Lower SES and Black minority patients were younger and had more comorbidities. Surgical need increased with age. Women had greater surgical need and provision than men. Geographical inequality had reduced in Scotland, but a north-south divide persists in England. Rural areas received greater provision relative to need, despite increased travel for care. In all, access inequalities remain widespread and policy change driven by research is needed.